Peran Organisasi Santri dalam Membangun Kesadaran Berdisiplin Pada Santri - Aminudin; Kasudin; Husnal Khalidah, Hanim; Tamsikuddin; Dzuriyat, Masduki (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
Discipline is an important thing in the education process, so this research aims to explore how a Santri organization can form Santri awareness in carrying out discipline to be able to carry out all activities regularly. Santri discipline awareness cannot just grow, but needs to be habituated, it is hoped that Santri organizations can encourage members to grow organizational awareness to be able to help run education well. This research uses qualitative research with a description method where data is obtained from interviews with the head of the Santri organization, the organization's supervisory council, and several Santri as members which we then describe using The result is that the Santri organization has a role in increasing the awareness of Santri discipline by interacting directly with members in carrying out the discipline that has been stipulated in the Tengko which is read as a reference for the regulations that must be obeyed by all Santri in the course of carrying out existing programs as a basic basis and being guided directly by the organizational supervisory council (MPO) with the supervision of the leadership and director.